ANALISA PERBANDINGAN KINERJA FITUR MIKROTIK CAPSMAN DENGAN KONFIGURASI TUNNEL DAN TANPA MENGGUNAKAN TUNNEL PADA ROUTER MIKROTIK RB951-2N - Indra Warman, S.Kom., M.Kom; Nofrizal (ITP Press, 2016)
CAPsMAN is one of the latest features of the Mikrotik Router, which is used to control many Access Point centrally. If a company / agency / agencies have dozens or hundreds of Access Point, then configure the IP address, gateway, DNS, frequency, channel, and SSID will be difficult to set up, because the configuration must be done on each Access Point. Therefore it takes a technique that can control the Access Point centrally, this technique is called with CAPsMAN. By using CAPsMAN, then control tens or hundreds Access Point will be much easier, because the wireless configuration can be performed on CAPsMAN MikroTik Router. CAPsMAN MikroTik Router technology in the implementation of security can not stand alone, thus requiring additional technology within the security of data packets being passed to a wireless hotspot network. One additional appropriate technology solutions in the security of the data packets on the network is a wireless Access Point Tunnel technology. Aim of this research to determine the comparative performance testing related features CAPsMAN Mikrotik download configuration data without using the tunnel and the tunnel on Router Mikrotik RB951-2N. In EoIP tunnel there is additional data packet header of 42 bytes of each packet of data that is passed. In this case it can be concluded that the speed of data packets being passed to a wireless network without the tunnel faster than using the tunnel. While the download test data is extracted two kinds of samples of data, that is data ISO and RAR with an average difference of 3 minutes 6 seconds with a capacity of 61.66 Kbps bandwidth.